What We Talk About When We Talk About Development? A Review - Dewa Gede Sidan Raeskyesa (Jurnal Ilmu Manajemen & Ekonomika, 2018)
The purpose of this research is to revisit the meaning of development by seeking to answer the question; what is development? Also, we question whether the common and old wisdom of development objectives, economic growth (GDP), should continue to be the focus of studies. It concludes that development is when human aspects are become the objectives